Geotechnical Properties of Malaysian Organic Soils: Case Study in Batu Pahat, Johor - Ling, Felix N. L.; Kassim, Khairul A.; A. Karim, A. Tarmizi; Tan, C. K.; Tiong, Kenney P. C. (International Journal of Integrated Engineering, 2014)
Subsurface exploration is required before any development project in order to gain an understanding of the characteristics of the material that one will encounter. The type of the tests and exploration are normally specified based on the design requirement in accordance to respective code of practice. In general, the physical properties and strength of the material are important in civil engineering applications. However, the chemical contents and organic contents are only specified sometimes when necessary despite the fact that the physical and strength of the material are closely related to its chemical properties and organic contents. In most construction works, the top soil and peat soil which are highly organic will be removed prior to carrying out construction work which resulted in exposing the bottom layer of soil. Hence, the aim of this study is to determine the geotechnical properties of the organic soils at the interface layer of peat soil and inorganic soil which normally exposed after removing top soil and peat soil at the surface. The physical & chemical properties, strength and organic contents of the soils are determined in accordance to the BS1377:1990 and BS ISO 13320:2009. Three locations which are identified to be rich in organic soils namely Parit Nipah, Parit Sidek and Batu Puteh of Batu Pahat, were chosen in this case study. These locations are found to be difference geographically. The soil samples were collected using a peat auger at Parit Nipah and Batu Puteh while undisturbed tube sampler was used at Parit Sidek because the soil is too stiff to be sampled using peat auger. The findings of this study showed that the physical properties of the soil are strongly correlated with its organic content. However, the chemical properties and strength of the soil is found to be site dependent and poorly correlated to its organic content.